Alloparenting is associated with reduced maternal lactation effort and faster weaning in wild chimpanzees. Issue 11 (November 2016) - Bădescu, Iulia; Watts, David P.; Katzenberg, M. Anne; Sellen, Daniel W.
Abstract : Alloparenting, when individuals other than the mother assist with infant care, can vary between and within populations and has potential fitness costs and benefits for individuals involved. We investigated the effects of alloparenting on the speed with which infants were weaned, a potential component of maternal fitness because of how it can affect inter-birth intervals, in wild chimpanzees ( Pan troglodytes schweinfurthii ) at Ngogo, Uganda. We also provide, to our knowledge, the first description of alloparenting in this population and present a novel measure of the contribution of milk to infant diets through faecal stable nitrogen isotopes (δ 15 N). Using 42 mother–infant pairs, we tested associations of two alloparenting dimensions, natal attraction (interest in infants) and infant handling (holding, carrying), to the proportion of time mothers spent feeding and to maternal lactation effort (mean nursing rates and mother–infant δ 15 N differences). Neither natal attraction nor infant handling was significantly associated with feeding time. Infant handling was inversely associated with both measures of lactation effort, although natal attraction showed no association. Alloparenting may benefit mothers by enabling females to invest in their next offspring sooner through accelerated weaning. Our findings emphasize the significance of alloparenting as a flexible component of female reproductive strategies in some species.